Human Embryonic Stem Cell-Derived Oligodendrocyte Progenitors Aid in Functional Recovery of Sensory Pathways following Contusive Spinal Cord Injury - All, Angelo H. (Public Library of Science, 2012)
BACKGROUND: Transplantations of human stem cell derivatives have been widely investigated in rodent models for the potential restoration of function of neural pathways after spinal cord injury (SCI). Studies have already demonstrated cells survival following transplantation in SCI. We sought to evaluate survival and potential therapeutic effects of transplanted human embryonic stem (hES) cell-derived oligodendrocyte progenitor cells (OPCs) in a contusive injury in rats. Bioluminescence imaging was utilized to verify survivability of cells up to 4 weeks, and somatosensory evoked potential (SSEPs) were recorded at the cortex to monitor function of sensory pathways throughout the 6-week recovery period. PRINCIPAL FINDINGS: hES cells were transduced with the firefly luciferase gene and differentiated into OPCs. OPCs were transplanted into the lesion epicenter of rat spinal cords 2 hours after inducing a moderate contusive SCI. The hES-treatment group showed improved SSEPs, including increased amplitude and decreased latencies, compared to the control group. The bioluminescence of transplanted OPCs decreased by 97% in the injured spinal cord compared to only 80% when injected into an uninjured spinal cord. Bioluminescence increased in both experimental groups such that by week 3, no statistical difference was detected, signifying that the cells survived and proliferated independent of injury. Post-mortem histology of the spinal cords showed integration of human cells expressing mature oligodendrocyte markers and myelin basic protein without the expression of markers for astrocytes (GFAP) or pluripotent cells (OCT4). CONCLUSIONS: hES-derived OPCs transplanted 2 hours after contusive SCI survive and differentiate into OLs that produce MBP. Treated rats demonstrated functional improvements in SSEP amplitudes and latencies compared to controls as early as 1 week post-injury. Finally, the hostile injury microenvironment at 2 hours post-injury initially caused increased cell death but did not affect the long-term cell proliferation or survival, indicating that cells can be transplanted sooner than conventionally accepted.